Welcome to Lagos - Onuzo, Chibundu (New York : Catapult, 2018)
Choosing to abandon his post when he is ordered to kill civilians, Nigerian army officer Chike Ameobi becomes the leader of a band of runaway rebels, each of whom reveals their difficult experiences that drove them to seek better lives.
Keywords: Life change events -- Fiction; Lagos (Nigeria) -- Fiction; Lagos (Nigeria) -- Fiction